Threshold concepts in undergraduate engineering: Exploring engineering roles and value of learning - Male, S.; Bennett, Dawn (Engineers Media Pty Ltd., 2015)
Threshold concepts are transformative disciplinary concepts. They are critical to students’ progress and often troublesome for students. In this study we explored two potential threshold concepts: namely “roles of engineers” and “value of learning”. Adopting a workshop format, the study trialled strategies that might help students overcome these threshold concepts. During the workshops, second-year students at an Australian university considered their motivations for studying engineering, their perceptions of engineering work, and their life and career identities at that point and into the future. Questions aligned with each activity were designed to determine whether students found these considerations transformative or troublesome. Analysis of students’ responses using a threshold concept framework revealed the students to be troubled by their lack of insight about the characteristics of engineering work. Students were also troubled by perceived gaps between the attributes of engineers and their own personal attributes. Further, students sensed a lack of alignment between engineering work, their career goals, and components of their engineering studies. The study draws attention to the need and opportunities for engineering educators to facilitate the development of students’ career preview, and to enhance their motivation to learn by linking career relevance to each unit of study.